Rapid fabrication of robust, washable, self-healing superhydrophobic fabrics with non-iridescent structural color by facile spray coating. Issue 14 (24th January 2017) - Zeng, Qi; Ding, Chen; Li, Qingsong; Yuan, Wei; Peng, Yu; Hu, Jianchen; Zhang, Ke-Qin
Abstract : An amorphous photonic structure dyeing system has been fabricated which endows non-iridescent color fabrics with color-tunable, robust, washable, self-healing and superhydrophobic properties by spray coating technique and heat treatment. Abstract : Robust, washable, and self-healing superhydrophobic fabrics with non-iridescence structural colors were prepared by a one-step spray coating technique using easily available materials: polyacrylate (PA) adhesive, monodisperse poly(styrene-methyl methacrylate-acrylic acid) (P(St-MMA-AA)) colloidal microspheres, and carbon black (CB). The color of the coated fabrics could be tuned as violet, green or red by just varying the size of the microspheres, and this method was effective in enhancing the fastness of the structural color on fabrics; for example, the coated fabrics could repeatedly withstand standard laundry, expedite laundry, and even supersonic vibrating cleaning without apparent color fading. In addition, the as-formed fabrics maintained superhydrophobicity with a high contact angle (>150°). The coated fabrics could also restore its super liquid-repellent property by a short-time heating treatment or room temperature ageing after being tentatively damaged. This simple but effective coating method may facilitate the development of special functional clothing for various applications.